FLORID ERUPTIVE XANTHOMAS IN A FAMILIAL HYPERTRIGLYCERIDEMIA PATIENT - Naidu, Thaalitha; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Eruptive xanthomas can be an early indicator of lipid disorders, occurring in approximately 8.5% of patients with severe hypertriglyceridemia. CASE A 27-year-old Malay male, with a history of Type 2 Diabetes Mellitus and Dyslipidemia since age 19, presented for treatment after being lost to follow-up. He reported osmotic symptoms, weight loss and recurrent severe epigastric pain radiating to the back. He is a teetotaler, heavy smoker (13 pack-years), with poor dietary habits and frequent high-fat, high-carbohydrate meals. Family history includes diabetes and dyslipidemia in both parents. On examination, BMI was 27 kg/m², waist circumference 80 cm and blood pressure 144/91 mm Hg. Crops of 2–5 mm yellow nodules were present over the elbows, buttocks, knees, lateral malleolus, and interphalangeal joints, along with yellowish papules over palms and back, suggestive of eruptive xanthomas. There was no arcus senilis or xanthelasma. Other systemic examinations were unre- markable. Fundoscopy showed no lipemia retinalis or diabetic retinopathy. Investigations revealed markedly elevated Total Cholesterol (TC) 15.89 mmol/L, Triglycerides (68.44 mmol/L), low HDL (0.61 mmol/L), with invalid LDL values. HbA1c was 10.7%, with mild transaminitis, proteinuria and CKD stage 2 (eGFR 61 mL/min/1.73 m2). Amylase, TSH and other biochemical tests were normal. ECG and echocardiogram were normal. Abdominal imaging revealed fatty liver without chronic pancreatitis. He was admitted for triglyceride lowering with IV insulin infusion and started on a low-calorie diabetic diet. Medi- cations included Dapagliflozin 10 mg OD, Metformin 1 g BD, Rosuvastatin 40 mg ON, fenofibrate 145 mg ON and Omega-3 fatty acids 3600 mg/day. At one-month follow-up, lipid levels improved (TC 3.81 mmol/L, TG 8.95 mmol/L, HDL 0.8 mmol/L), though LDL remained invalid. He is planned for PCSK9 inhibitor initiation and was referred to dermatology for xanthomas. Genetic testing is also scheduled. CONCLUSION Early recognition and management of severe hypertri- glyceridemia is vital to reduce risks of acute pancreatitis as well as long-term cardiovascular complications.